ANALISIS SISTEM PENGELOLAAN REKAM MEDIS RAWAT INAP RUMAH SAKIT UMUM DAERAH PERDAGANGAN TAHUN 2019 - Sahat Tua Irwanto Sidauruk (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2020)
Medical Records are written evidence of the service process that provided by doctors and other health professionals to patients. The incompleteness and delay in filling out the medical record file and the delay in returning the medical record file are thought to be related to the lack of ability of the hospital management to manage the medical record. This study aims to analyze the Inpatient Medical Record Management System of Perdagangan General Hospital in 2019 and to overcome existing obstacles and improve service quality in the medical record department. This study used a qualitative method or approach with a case study design with informants selected based on the problems and research objectives of all 1 general practitioners, 2 specialist doctors, the Secretary of the Perdagangan General Hospital, Head of the Medical Records Room and 1 Medical Committee. The results showed that the incomplete rate of inpatient medical records at Perdagangan General Hospital is still high, 34,79%. The responsibility of doctors in the completeness of inpatient medical records at Perdagangan General Hospital is still lacking. Based on the interview recording and observation found that knowledge, motivation, attitude and leadership are influence factors on completing of inpatient medical records at the Perdagangan General Hospital and the lack of supervision from the hospital management regarding the management of medical records. It is recommended to the hospital to have clear SOP for all personnel to facilitate the work and carry out the process of completing medical record filling and evaluation, and the hospital management need to supervise all components of the hospital, especially doctors in filling medical records.